2020
DOI: 10.4038/jnsfsr.v48i2.8952
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antifungal efficacy of selected essential oils in controlling fungi associated with the stem-end rot disease of mango (cv. Karutha Colomban) fruits and characterisation of antifungal components

Abstract: Karutha Colomban is one of the most delightful mango varieties popular among Sri Lankan consumers. A signifi cant postharvest loss of mango takes place every season due to diseases including stem-end rot (SER), which is caused by a group of endophytic fungal pathogens. In this research, in vitro antifungal effi cacy of diff erent concentrations of essential oils of basil, clove, and cinnamon were evaluated for their ability to control SER causing fungal pathogens of mango (cv. Karutha Colomban) as bio-safe alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
5
1
Order By: Relevance
“…Contrary to Sukatta et al (2008), the present study showed that clove oil was successful in inhibiting growth of L. theobromae at concentrations lower than 10 μL/plate. According to a similar in vitro disc volatilization assay carried out by Kodituwakku et al (2020b), clove and cinnamon oils inhibited the growth of SER pathogen L. theobromae isolated from mango at a concentration of 2 μL/plate, which is comparatively lower than the inhibitory concentrations reported in the present study. This might be due to differences in composition of the same oil, depending on its origin.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…Contrary to Sukatta et al (2008), the present study showed that clove oil was successful in inhibiting growth of L. theobromae at concentrations lower than 10 μL/plate. According to a similar in vitro disc volatilization assay carried out by Kodituwakku et al (2020b), clove and cinnamon oils inhibited the growth of SER pathogen L. theobromae isolated from mango at a concentration of 2 μL/plate, which is comparatively lower than the inhibitory concentrations reported in the present study. This might be due to differences in composition of the same oil, depending on its origin.…”
Section: Discussioncontrasting
confidence: 73%
“…GC-MS conducted by Kodituwakku et al (2020b) revealed that eugenol (79.11%), β-caryophyllene (9.07%), caryophyllene oxide (0.40%) and eugenyl acetate (0.20%) are the major bioactive components of clove oil. Eugenol, which is the dominant component of clove oil as reported in many studies, varies from 30 -95% depending on the plant part used for extraction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antifungal efficacy of cinnamon oils is mainly due to the presence of eugenol and cinnamaldehyde as major constituents in cinnamon leaf and bark oils respectively (Abeywickrama, 2009). According to a recent gas chromatography-mass spectroscopy (GC-MS) analysis, cinnamon leaf oil mainly consisted of eugenol (63.76%), benzyl benzoate (3.61%), β-caryophyllene (2.48%), eugenol acetate (2.27%), (E)-cinnamaldehyde (1.37%), linalool (1.27%), and cinnamyl acetate (1.08%) (Kodituwakku et al, 2020a). GC-MS analysis of cinnamon bark oil showed a higher percentage of (E)-cinnamaldehyde (72.18%) followed by cinnamyl acetate (5.16%), eugenol (4.82%), β-caryophyllene (3.95%), linalool (3.69%), and benzyl benzoate (1.51%) as major constituents (Kodituwakku et al, 2020a).…”
Section: Pathological Propertiesmentioning
confidence: 99%
“…Different studies on essential oils of Cinnamomum verum J.Presl (cinnamon) have revealed that it has fungistatic and fungicidal properties against pathogenic fungi. Kodituwakku et al (2020a) reported that cinnamon leaf and bark oils effectively inhibited SER causing fungal pathogens of mango cv. 'Karthakolomban'.…”
Section: Introductionmentioning
confidence: 99%